Bird O’rama - Tengku Azizan, Tengku Rinafli Putra; Abu, Jalila (Universiti Putra Malaysia Press, 2015)
The most visible animals on earth are birds. Flying adaptations in birds garner much attention in the field of science and art. The mechanics of flying, the fluidity of its flight pattern,the accuracy of landings, the arrangement of its different types of feathers, the trans-boundary nature in which they travel across continents and oceans; have been subjects of intellectual discourse over the years by both scientists and artists.